2017
DOI: 10.4066/2529-8046.100023
|View full text |Cite
|
Sign up to set email alerts
|

Peanut (Arachis hypogaea L.) yield and its components as affected by N-fertilization and diazotroph inoculation in Toshka desert soil-South Valley-Egypt.

Abstract: Peanut (Arachis hypogaea L.) yield and its components as affected by N-fertilization and diazotroph inoculation in Toshka desert soil-South Valley-Egypt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…These studied results could be the correlative cause between CM and Rhizobium inoculum with roots of previous groundnut crops [25]. Biomass and matureness of groundnuts were positively improved by Co-application of poultry manures, Rhizobium in the next crops [26]. Number of highest nodules observed in treatments with CM amendment which showed that N-fixation increased under organic nutrients as peanut tend to respond on fixed -N, when the CM rate may significantly depend on the nutrient contents of CM and other essential elements in crop soil [27].…”
Section: Effect Of CM Rhizobium Sp and Npk Fertilizer On Plant Height...mentioning
confidence: 66%
“…These studied results could be the correlative cause between CM and Rhizobium inoculum with roots of previous groundnut crops [25]. Biomass and matureness of groundnuts were positively improved by Co-application of poultry manures, Rhizobium in the next crops [26]. Number of highest nodules observed in treatments with CM amendment which showed that N-fixation increased under organic nutrients as peanut tend to respond on fixed -N, when the CM rate may significantly depend on the nutrient contents of CM and other essential elements in crop soil [27].…”
Section: Effect Of CM Rhizobium Sp and Npk Fertilizer On Plant Height...mentioning
confidence: 66%
“…Bradyrhizobium sp. was used to inoculate Arachis hypogaea plants in the past successfully, and this led to a significant increase in nodules—about 252 nodules plants compared to Enterobacter inoculation for nodules fresh weight dry weight, shoot, root, plant new weight, and peanuts yield content, respectively [ 51 ],oil percentage, protein percentage, nitrogen, phosphorus, and potassium content all rose during the inoculation of seeds [ 52 ]. In another study, siderophores producing P. fluorescens isolate, C7, recorded enhanced Arabidopsis thaliana plant growth by mobilizing sufficient iron uptake to plants [ 53 ].…”
Section: Discussionmentioning
confidence: 99%